Karakteristik dan tingkat partisipasi petani di Desa Tonongrejo, Jawa Timur - Latarus Fangohoi; Yohanes Yan Makabori; Yuliana Ataribaba (Fakultas Pertanian Universitas Yudharta Pasuruan, 2022)
Introduction: The purpose of this research is to find and explain the characteristics of farmers and the level of participation in farmer groups and to explain the correlation of characteristics internally and externally in Tonongrejo Village, East Java. Methods: By applying of census sampling in descriptive, sample is about sixty-two farmer members. Rank Spearman test is to see the correlation between dependent and independent variable. Input of system approach: supposing of H0 is no link among x and Ha has link among x. Both refers to internal and external factors to farmer participation. T-score (mean = 50 and deviation = 10) as score standard to see the distribution of extensive evaluation. Data collected used questioner, observation, and interview. Results: The result is farmer participation of 84% in planning and implementing, in evaluating of 82%, in enjoyed the outcome of 89%. Conclusion: Characteristics farmers and participation prefer to age, farming time, land area and leadership. The relation of farmer characteristic and participation rate is one-way.